Chemical Weapons and the International Criminal Court. Issue 3 (July 2014) - Zimmermann, Andreas; Şener, Meltem
Abstract : When the contracting parties to the Rome Statute establishing the International Criminal Court met in Kampala in 2010 to discuss possible amendments to the statute, the main focus was, and has thereafter remained, on the crime of aggression. In addition to amending the statute to include the crime of aggression, however, the contracting parties amended Article 8 of the statute to include a broader range of war crimes in noninternational armed conflicts over which the ICC can have jurisdiction—inter alia, by including the use of chemical weapons. Although the latter amendment received much less attention from both the Kampala drafters and outside observers than the former, it is the use of chemical weapons that has come most quickly into play in world events. In particular, the use of chemical weapons by Syrian government forces in 2013 (and perhaps subsequently) has acutely raised questions concerning the extent of the ICC's treaty-based jurisdiction, both under the unamended text of the Rome Statute or in situations where the amendment to Article 8 applies. These events have also provoked consideration concerning the Security Council's legal powers to extend the ICC's jurisdiction to certain crimes involving chemical weapons that would otherwise be beyond its subject matter jurisdiction. These questions are considered in this Note.